1966
DOI: 10.1002/macp.1966.020940124
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl polymerization. 120. Mutual copolymerization of p‐substituted styrenes through radical mechanism

Abstract: The radical mutual copolymerization of p-substituted styrenes, such as p-methoxy-, p-chloro-, p-bromo-, p-cyanostyrene, and styrene was carried out with one another at 30°C. in the dark. As initiator, azobisisobutyronitrile was used. The plots of the copolymerization rates against HAMMETT'S a values showed no linear relationships, and the concave curves were obtained therefrom. The relative reactivities of p-substiluted styrenes with a definite p-substituted polystyryl radlcal, which were shown by the reciproc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…DPPS shows a strong tendency to homopolymerize, while St preferentially copolymerizes with DPPS. This tendency is probably due to the electron‐withdrawing character of the diphenylphosphine substituent, and is in line with the reactivity of other p ‐substituted styrenes with electron‐withdrawing substituents, such as p ‐cyanostyrene ( r StCN = 1.2, r St = 0.19) or p ‐chlorostyrene ( r StCl = 1.1, r St = 0.55) …”
Section: Resultssupporting
confidence: 70%
“…DPPS shows a strong tendency to homopolymerize, while St preferentially copolymerizes with DPPS. This tendency is probably due to the electron‐withdrawing character of the diphenylphosphine substituent, and is in line with the reactivity of other p ‐substituted styrenes with electron‐withdrawing substituents, such as p ‐cyanostyrene ( r StCN = 1.2, r St = 0.19) or p ‐chlorostyrene ( r StCl = 1.1, r St = 0.55) …”
Section: Resultssupporting
confidence: 70%
“…11 Relative reactivity of p-substituted p-methylstyrenes toward maleic anhydride radical were related to p-a + relation and a reaction constant p=-1.13 was reported. 12 Since the maleic an-162 hydride radical probably has a more electrophilic character than the acrylonitrile radical, the polar effect of alkyl substituents may be much smaller than the actual difference in reactivity.…”
Section: Ch3 »Et N-pr N-bu»i-pr>s-bu»t-bumentioning
confidence: 99%
“…These results suggest that some synergistic dipole-dipole interaction between captive and dative moieties of MAA and EAA monomers and polymers seems to play an important role, not only in the termination but also in other elemental reaction processes, including the propagation. It has been reported that the polarity of styrene derivatives affects the copolymerization reactivity 18 and also the homopolymerization rate 19 even in a radical mechanism. However, there is little work concerning the dependence of the molecular weight on monomer polarity in the field of normal radical polymerization in a homogeneous solution.…”
Section: Resultsmentioning
confidence: 99%